L’expression du degré dans la détermination du nom. - Catherine Moreau (Corela)
The study focuses on a particular way of determining a noun, which is to express the degree associated with this noun. This is an utterer-centered approach in which we present the operation of determination as a referential process through delimitation, which does not always demand a specific marker of nominal determination. We show that great quantity when associated with emphasis comes close to expressing degree, semantically speaking. However in order to express degree by itself, it is necessary to work on a gradable property with an oriented gradient linked to it. We show first that quantity and degree are closely linked in scalar comparison (more; less; as much…as), then that high degree comes from the use of an attracting center and the orientation of the gradient. This gives rise to relative and absolute superlatives such as those found in the discourse in study: the best; very; so; such and this.